Positive psychological outcomes following Antarctic deployment - Blight, S; Norris, K (The Polar Journal, 2019)
Previous Antarctic research has been criticised for emphasising a disease producing (pathogenic) approach, as opposed to a health and well-being (salutogenic) approach. Moreover, anecdotal and empirical evidence suggests that there are positive psychological outcomes resulting from Antarctic deployment. The primary aim of the current study was to examine post-expedition growth following Antarctic deployment. There were 225 participants who completed an online survey comprising a modified Post-Experience Change Inventory. The results indicated that Antarctic expeditioners experienced post-expedition growth in a number of domains, with personal strength the highest perceived category of personal growth and spiritual and existential change the least likely to result in perceived growth. It was concluded that long-term positive after effects result from Antarctic employment. The results of the current study may help inform future recruitment and training efforts in Antarctic employment as well as other isolated and confined environments.